Clinicohistological Profile of Cutaneous Tuberculosis in Central Nepal - Mathur, M; Pandey, SN (Kathmandu University Medical Journal, 2015)
Background There are few studies on cutaneous tuberculosis in Nepal.Objective To analyse the epidemiological, clinical and histological patterns of cutaneous TB over the past 5 years.Method Patients with cutaneous tuberculosis diagnosed from January 2010 to December 2014 at College of Medical Sciences, Chitwan, Nepal were included in the study. Chest radiography, routine investigations and screening for HIV was performed in all cases.Result A total of 47 clinical cases of cutaneous tuberculosis were diagnosed. The most commonly affected age group was 41-50 years. Male to female ratio was 1.5:1. Duration of cutaneous tuberculosis ranged from 1 month to 33 years. Lupus vulgaris was the most common clinical type (64%), followed by tuberculosis verrucosa cutis (19%). Two cases (4%) were diagnosed as papulonecrotic tuberculid. Overall, the most common site of involvement was extremities (55%) followed by head and neck, trunk, and perianal region. Histopathologic features of epitheloid cell granuloma with Langhans type giant cells were seen in 89% of cases, and in remaining 11% cases, chronic inflammatory dermatitis and nonspecific chronic dermatitis were observed.Conclusion M Tuberculosis is endemic in Nepal and the incidence of cutaneous tuberculosis at our centre was 0.1%. Lupus vulgaris was the most common type followed by tuberculosis verrucosa cutis in our study. Cutaneous tuberculosis can be accompanied by tuberculosis in internal organs and hence should be looked for. Clinicopathologic correlation is necessary to make a proper diagnosis.Kathmandu University Medical Journal Vol.12(4) 2014; 238-241